China as an Alternative Source of FDI: Analyzing The Cases in Indonesia - Said Rivaldi Assagaf; Aridiva Firdharizki; Hernando Wisnumurti (Ilomata International Journal of Social Science, 2023)
As China is strengthening its global position, it has gradually begun to exert its influence in the world economy. This can be observed in its move as investors to countries on the Asia and Africa continents, a position used to be dominated by western countries and institutions, as seen in the International Monetary Fund . However, China’s rising economy and influence have allowed itself to become an alternative source of funding for many countries formerly dependent on the International Monetary Fund, on other western related countries or on particular institutions due to the restrictions the loans carry. Countries such as Indonesia views China as an alternate source for their foreign direct investment, manifested in the construction of the Indonesian High Speed Rail project, the projects of Huawei, and in the Indonesian energy sector. China’s potency to enter into and expand in Indonesia is supported by the lack of restrictions towards the funding, if compared to the ones provided by western institutions. As a result, China has successfully presented itself as an alternate choice for many countries who wish to seek financial support to further their development.